Update on the Genetics of and Systemic Therapy Options for Combined Hepatocellular Cholangiocarcinoma - Azizi, Alexander A.; Hadjinicolaou, Andreas V.; Goncalves, Carla; Duckworth, Adam; Basu, Bristi (Frontiers in Oncology, 2020)
Combined hepatocellular-cholangiocarcinoma (cHCC-ICC) is an uncommon and aggressive form of primary liver cancer. Currently, there are no international guidelines for optimal management. For localised tumours, radical resection represents the preferred treatment option, whereas for advanced tumours, systemic therapies recommended for intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) are often selected. Emerging information from comparative cohort studies, genomic and transcriptomic data sets are starting to build a case for rationalised approaches to systemic treatment in the advanced setting specific to cHCC-ICC.